2016
DOI: 10.1016/j.chest.2015.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and the Lung

Abstract: A link between metabolic syndrome (MetS) and lung diseases has been observed in several cross-sectional and longitudinal studies. This syndrome has been identified as an independent risk factor for worsening respiratory symptoms, greater lung function impairment, pulmonary hypertension, and asthma. This review will discuss several potential mechanisms to explain these associations, including dietary factors and the effect of adiposity and fat-induced inflammation on the lungs, and the role of other comorbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
148
4
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(163 citation statements)
references
References 78 publications
6
148
4
5
Order By: Relevance
“…Suggested links include chronic inflammation, mitochondrial dysfunction,, Th17-induced neutrophilia, macrophage dysregulation, hormonal changes, lipid metabolism, insulin resistance, and body mechanics (Baffi et al, 2016; Chesne et al, 2014; Shore and Cho, 2016). Other well-described abnormalities in obesity and metabolic syndrome, accelerated formation of advanced glycation end products (AGEs) and alterations in arginine metabolism may also play a crucial role in asthma pathogenesis and may be modulated by the anti-inflammatory incretin, GLP-1 (Figure 1) (Holguin, 2013; Milutinovic et al, 2012; Ojima et al, 2013; Singh et al, 2015; Uribarri et al, 2015).…”
Section: Obesity-related Asthmamentioning
confidence: 99%
“…Suggested links include chronic inflammation, mitochondrial dysfunction,, Th17-induced neutrophilia, macrophage dysregulation, hormonal changes, lipid metabolism, insulin resistance, and body mechanics (Baffi et al, 2016; Chesne et al, 2014; Shore and Cho, 2016). Other well-described abnormalities in obesity and metabolic syndrome, accelerated formation of advanced glycation end products (AGEs) and alterations in arginine metabolism may also play a crucial role in asthma pathogenesis and may be modulated by the anti-inflammatory incretin, GLP-1 (Figure 1) (Holguin, 2013; Milutinovic et al, 2012; Ojima et al, 2013; Singh et al, 2015; Uribarri et al, 2015).…”
Section: Obesity-related Asthmamentioning
confidence: 99%
“…Several studies have suggested that each of the individual components of the metabolic syndrome are indeed associated with asthma, independently of obesity [1820]. However, the relative contribution of each component of the metabolic syndrome to a more severe asthma phenotype has not been established, as recently reviewed by Baffi et al [21]. Whether components of the metabolic syndrome are also effect modifiers of the association between obesity and asthma is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The CMA provides oxygen and nutrients to the body. A link between metabolic syndrome (MetS code E88.81), or better to metabolic disorder (MetD), and lung diseases has been reported by several cross-sectional and longitudinal studies (as reviewed, recently, by Baffi et al [12]). The concept of MetS evolved over time to MetD; indeed, MetD is a complex disorder thought as a cluster of conditions sustaining a “ disorder in energy use and storage ” characterized by central obesity, dyslipidemia, high blood sugar levels (hyperglycemia), hypertriglyceridemia, and low high-density lipoprotein cholesterol levels.…”
Section: Introductionmentioning
confidence: 99%